Anemia Due to Heavy Menstrual Bleeding: A Literature Review - Shazia Tabassum, Rabeea Ssadaf, Nasreen Kishwar, Bushra Rauf, Samreen, Umaiyma Farhad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The aim of this study is to review the current guidelines regarding the management of HMB, including screening for anemia, Iron studies and iron-based and non-iron-based treatment of ID/IDA. Methods: The literature searched for this article included the latest Guidelines for HMB. The data was collected from authentic websites such as pubmed and well-known clinical guidelines from professional societies. Results: More than 50 guidelines throughout the world were searched and studied for this review. Among them 22 were selected for this review. 16 of these guidelines focused on screening of women with HMB for anemia. There were some inconsistencies concerning screening for ID with eleven of the 22 guidelines providing no recommendation for screening of Iron levels and four even strictly advising against screening for iron levels initially. Almost one third of the selected guidelines provided guidance for oral iron therapy as first line in ID, 4 guidelines provided guidance for use of IV iron replacement in severe anemia, non-responders to oral treatment and prior to surgery. 3 of the guidelines had HB threshold for selecting between oral and IV route while further 4 guidelines were of the view of transfusion in case of severe anemia. Conclusion: Although many of the guidelines are of the view to treat anemia due to HMB, there is lack of consensus regarding screening for ID and treatment with iron supplements, due to this most of the IDA related with HMB goes undiagnosed. Therefore, a proper guidance is required that addresses all the aspects of ID/IDA including screening, relevant tests and treatment in patient with HMB in order to optimize the health outcome of these patients. Keywords: Anemia, Blood, Menstrual Cycle, Surgery